The Pain Disability Questionnaire: a reliability and validity study The Pain Disability Questionnaire: estudio de confiabilidad y validación The Pain Disability Questionnaire: um estudo de confiabilidade e validade - Patrícia Cantu Moreira Giordano; Neusa Maria Costa Alexandre; Roberta Cunha Matheus Rodrigues; Marina Zambon Orpinelli Coluci (Universidade de São Paulo, 2012)
The goal of this study was to translate and adapt The Pain Disability Questionnaire (PDQ) to Brazilian Portuguese, as well as to assess its psychometric properties and practicability. The following methodological steps were followed: translation, synthesis, back-translation, expert committee assessment and pre-test. The psychometric properties were assessed through the application of a questionnaire to 119 patients with chronic musculoskeletal disorders. The results indicated the reliability of the instrument, with a Cronbach's alpha coefficient of 0.86, and high stability in the test-retest. A moderate correlation was found between the PDQ scores and the numerical pain scale. Negative correlations were found between the Spitzer Quality of Life Index and the functional condition, psychosocial component and total PDQ score. Construct validity demonstrated significant difference in PDQ scores between symptomatic and asymptomatic individuals. The PDQ revealed fast application and easy understanding. The results indicated a successful cultural adaptation and reliable psychometric properties. El objetivo de este estudio fue traducir y adaptar el Cuestionario The Pain Disability Questionnaire (PDQ) para el portugués de Brasil, evaluando sus propiedades psicométricas y la usabilidad. Fueron seguidos los siguientes pasos metodológicos: traducción, síntesis, retrotraducción, evaluación por un comité de expertos y realización de una prueba piloto. Las propiedades psicométricas fueron evaluadas por la aplicación del cuestionario en 119 pacientes con lesiones musculares. Los resultados indican la confiabilidad del instrumento con el coeficiente alfa de Cronbach de 0,86, y alta estabilidad en la prueba piloto. Una correlación moderada se encontró entre las puntuaciones de la PDQ y la escala numérica del dolor. Correlaciones negativas fueron observadas entre el Spitzer Quality of Life Index y la condición funcional, el componente psicosocial, y la puntuación total de la PDQ. La validez del constructo demostró una diferencia significativa en las puntuaciones del PDQ entre sujetos sintomáticos y asintomáticos. El PDQ demostró ser rápido y comprensible. Los resultados indicaron una exitosa adaptación cultural y propiedades psicométricas confiables. O objetivo deste estudo foi traduzir e adaptar The Pain Disability Questionnaire (PDQ) para o português do Brasil, avaliar suas propriedades psicométricas e praticabilidade. Os seguintes passos metodológicos foram seguidos: tradução, síntese, retrotradução, avaliação por comitê de especialistas e pré-teste. As propriedades psicométricas foram avaliadas pela aplicação do questionário a 119 pacientes com lesões musculoesqueléticas crônicas. Os resultados indicaram a confiabilidade do instrumento com o coeficiente alfa de Cronbach de 0,86, e alta estabilidade na aplicação do teste-reteste. Uma correlação moderada foi encontrada entre os escores do PDQ e a escala numérica de dor. Correlações negativas foram encontradas entre o Spitzer Quality of Life Index e a condição funcional, componente psicossocial e escore total do PDQ. A validade de construto demonstrou diferença significativa nos escores do PDQ entre indivíduos sintomáticos e assintomáticos. O PDQ mostrou aplicação rápida e fácil entendimento. Os resultados indicaram sucesso na adaptação cultural e propriedades psicométricas confiáveis.